Exploring role of polyester composites in biocomposites for advanced material technologies: a comprehensive review - Dag, Mustafa; Aydogmus, Ercan; Arslanoglu, Hasan; Yalcin, Zehra Guelten (Taylor & Francis Inc, 2025)
This study represents the culmination of our efforts to explore the crucial role of polyester composites in the field of biocomposites, highlighting their importance in advanced materials technologies. Our primary objective has been to thoroughly elucidate the significance of polyester composites within biocomposites, with a detailed examination of their impact on advanced material technologies. Through this research, we have meticulously investigated the properties of polyesters derived from biodegradable polymers, analyzing their intricate structure-property relationships and potential applications in bio-based production. To drive the industrial adoption of bio-based polyesters, our work emphasizes the need for developing economically viable production methodologies, exploring ecologically sustainable and effective material designs, and advocating for robust policy support to facilitate the commercialization of bio-based polyesters. We propose that future research should focus on the innovation of novel bio-based monomers as sustainable raw material sources, the design of diverse polyester structures utilizing material genome technology, and a comprehensive understanding of the degradation processes and long-term performance of bio-based polyesters. The advancement in this domain relies on interdisciplinary collaboration across materials science, engineering, and chemistry. Our findings underscore that through such interdisciplinary cooperation, a broader spectrum of bio-based polyester products can be developed, thereby expanding their industrial applications. In this context, our investigation aims to contribute to the advancement of sustainable materials and their more effective integration into future material technologies. Graphical Abstract
Keywords: Advanced material; biocompatibility; polyester biocomposite; sustainable